2005
DOI: 10.1021/bi050876o
|View full text |Cite
|
Sign up to set email alerts
|

Histone Release during Transcription:  Acetylation Stabilizes the Interaction of the H2A−H2B Dimer with the H3−H4 Tetramer in Nucleosomes That Are on Highly Positively Coiled DNA

Abstract: A high level of the post-translational modification, acetylation, is found on the N-terminal regions of the core histones H2A, H2B, H3, and H4 and is primarily located in the nucleosomes of active genes. An in vitro transcription system was applied, which utilizes T7 RNA polymerase and template DNAs that are either moderately or highly positively coiled, to determine whether acetylation alters the dynamics of histone displacement from these templates during transcription. To measure displacement, an excess of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 101 publications
(146 reference statements)
1
8
0
Order By: Relevance
“…Some notable examples of a direct structural effect of histone PTMs and nucleosomal structure are the electrostatic interaction between the H4 tail with respect to H2A/H2B on the adjacent nucleosome [31], the electrostatic interaction between H3K56ac and the DNA backbone [32], and the general destabilization of the nucleosome bound to positively supercoiled DNA by the hyperacetylated histones H3 and H4 [33]. The acetyl moiety removes the positive charge from lysines due to resonance effects of the carbonyl group, whereas the methyl moiety stabilizes charge by raising the acid dissociation constant (pKa) of the remaining acidic protons.…”
Section: Resultsmentioning
confidence: 99%
“…Some notable examples of a direct structural effect of histone PTMs and nucleosomal structure are the electrostatic interaction between the H4 tail with respect to H2A/H2B on the adjacent nucleosome [31], the electrostatic interaction between H3K56ac and the DNA backbone [32], and the general destabilization of the nucleosome bound to positively supercoiled DNA by the hyperacetylated histones H3 and H4 [33]. The acetyl moiety removes the positive charge from lysines due to resonance effects of the carbonyl group, whereas the methyl moiety stabilizes charge by raising the acid dissociation constant (pKa) of the remaining acidic protons.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the N-terminal tail of H2B itself is crucial for chromatin condensation25. Moreover, the H2B acetylation at the N-terminal end is important to maintain a stable structure of H2A–H2B dimers in the nucleosome26,27. Since the N-terminal domain of H2B including the S14 site exists outside of the nucleosome structure28, it could be susceptible to modification by phosphatases or kinases if left unprotected.…”
Section: Discussionmentioning
confidence: 99%
“…51.) The effect of histone acetylation on the histone acceptor ability of Nap1 has been substantiated in subsequent work (102), but the exact molecular mechanism requires further investigation. Acetylation may reduce the affinity of H2A/H2B for the H3/H4 tetramer or for the DNA ends in the nucleosome (the sites of H2A/H2B binding); alternatively, acetylation may change the affinity of H2A/H2B for Nap1.…”
Section: Nap Affects Transcription Initiation At Nucleosomesmentioning
confidence: 92%
“…A wealth of information about the possible involvement of Nap1 in transcription elongation comes from a series of careful in vitro transcription experiments in model systems that use polynucleosomal templates re‐constituted on linear or superhelical DNA molecules of different levels of superhelical stress (102, 111, 112).…”
Section: Nap1 Affects Transcription Elongation Through Nucleosomesmentioning
confidence: 99%